Enactment DDC Controller for Optimal Operation of Irrigation Drive Solar Pump –PVSYST’s - Nibedita Das (International Journal of Advanced Science and Technology, 2020)
In light of the rapid expansion of solar pumping grassland, there is an opportunity for a solution of Direct Digital Controller (DDC) and a closed loop control system coupled solar well storage pump control PV panel for clean irrigation smart and innovative energy technology. To harvest maximum power from a PV array, panel control model of the MPPT controller valve based solar pumps, PV cells are used to generate electricity, which is stored in rechargeable batteries for production of power for the system operation. This paper presents the performance of a solar PV pumping system for irrigation by taking account of a site location of Mathura, India. The DDC Excel@™ Calculator assisted to provide accurate data of hydraulic water harvesting solar pumping system which is executed in PVSYST’s software for analysis of that pump has been carried out. The aim of simulated pump using PVSSYST’s is to assess the working hours of pump, PV module, total volume of water capacity and energy generated by photovoltaic array, during annually are considered for performance analysis.